2015
DOI: 10.1021/jacs.5b00922
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Accumulation and Penetration of HPMA Copolymer–Doxorubicin Conjugates in 2D and 3D Prostate Cancer Cells via iRGD Conjugation with an MMP-2 Cleavable Spacer

Abstract: To enhance the accumulation and penetration of nanomedicines in tumor tissue, we developed and evaluated the biological properties of matrix metallo-proteinase 2 (MMP-2)-responsive N-(2-hydroxypropyl)-methacrylamide (HPMA) copolymer drugs and tumor-penetrating peptide conjugates (P-DOX-PLGLAG-iRGD). Two different spacers were used in the design: a lysosomally (cathepsin B) cleavable tetrapeptide GFLG spacer conjugated doxorubicin (DOX) to HPMA copolymer, and an MMP-2-degradable linker (PLGLAG) connected tumor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(88 citation statements)
references
References 38 publications
1
87
0
Order By: Relevance
“…In addition to the size‐transition discussed above,[13,33b,123] other strategies have also been explored to improve tumor penetration ability of nanomedicines, including functionalizing nanomedicines with tumor penetrating peptides and modulating tumor extracellular matrix . Tumor‐homing and ‐penetrating cyclic peptide iRGD, tLyP‐1, PFVYLI (PFV) have been shown to enhance the tumor accumulation and penetration of nanomedicines, particularly tumor penetrating peptides containing a cryptic (R/K)XX(R/K) CendR element that must be C‐terminally exposed to trigger neuropilin‐1 (NRP‐1) binding, cellular internalization and malignant tissue penetration …”
Section: Approaches To Achieve the 3s Transitionsmentioning
confidence: 99%
“…In addition to the size‐transition discussed above,[13,33b,123] other strategies have also been explored to improve tumor penetration ability of nanomedicines, including functionalizing nanomedicines with tumor penetrating peptides and modulating tumor extracellular matrix . Tumor‐homing and ‐penetrating cyclic peptide iRGD, tLyP‐1, PFVYLI (PFV) have been shown to enhance the tumor accumulation and penetration of nanomedicines, particularly tumor penetrating peptides containing a cryptic (R/K)XX(R/K) CendR element that must be C‐terminally exposed to trigger neuropilin‐1 (NRP‐1) binding, cellular internalization and malignant tissue penetration …”
Section: Approaches To Achieve the 3s Transitionsmentioning
confidence: 99%
“…Since that publication there have been additional studies that have utilized the iRGD peptide with the chemotherapeutic agent doxorubicin (DOX) in cancer biology research. Follow-up studies by Peng et al reported that in an in vitro model of prostate cancer iRGD improved the penetrance of DOX into tumor cell lines (Peng and Kopeček, 2015). However, this improvement was only observed in a DOX/iRGD conjugated form.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor homing of the disulfide-bridged cyclic iRGD peptide follows the consecutive steps: the RGD sequence binds to αv integrins on tumor endothelium, then iRGD undergoes a proteolytic cleavage to expose the CendR motif (R/KXXR/K) that triggers neuropilin-1 (NRP-1)-mediated internalization into cells [20, 21]. These distinct attributes of iRGD have been utilized to improve the tumor targeting and internalization of imaging agents and drugs [22-29]. …”
Section: Introductionmentioning
confidence: 99%